Building community based arsenic mitigation response capacity in four upazilas of Bangladesh - Hossain, Md Zabed; Mahmud, Shah Noor; Jakariya, Md. (BRAC Research and Evaluation Division (RED), 2019)
BRAC in collaboration with DPHE and 'UNICEF implemented the project entitled "Building community based arsenic mitigation response capacity" during July 2001 to June 2002 in four upazilas named Barura, Haimchar, Bahanga, and Monirampur of Comilla, Chandpur, Faridpur, and Jessore districts respectively. The objectives ofthe project are to (i) raise awareness among the community (ii) determine the extent of arsenic contamination in all tubewell water in the project areas; and (iii) develop resource maps of different villages of the project area to locate safe water sources. The activities executed in the project were creation awareness among the people through training, workshop, formation of different types of arsenic mitigation committees, training for tubewell testing and blanket tubewell testing, providing technical advice on safe water and collation and dissemination of knowledge generated and lessons learnt. At the upazila level, upazila project co-ordinator ofBRAC actively participated at upazila monthly co-ordination meeting in order to appraise different stakeholders and government officials about activities and progress on arsenic mitigation. BRAe provided quarterly report to the co-ordination committee. A working committee was formed whereby local DPHE and BRAC project personnel worked together to plan and review different project activities and its progress. A total of85937 shallow tubewells, among those 21003,26339,3585 and 35010 in Bhanga, Barura, Haimchar, and Monirampur upazilas respectively were tested. Among the four upazilas the highest contamination was found in Bhanga (91 %) and the lowest was in Monirampur (51 %). A total of 378 deep hand set tubewells were tested in the project areas. Among these deep hand set tubewells only 14 (3.7%) were found to be contaminated with arsenic of above permissible 153 limit. In the four upazilas a total of 14989 irrigation wells were tested ofthose 70% were found contaminated. Field testing of the tubewells for arsenic was validated by laboratory analysis using AAS (Atomic absorption spectrophotometry). It was found that the field testers did reasonably well in testing the tubewells. The percentage of correctly tested tubewells (green-green and red-red) was 92% and 90-91 % respectively. There was no significant seasonal variation in concentration of arsenic in tubewell water. Achievement in fonnation of arsenic mitigation committees was 100% at the Upazila level to Ward level in all the four upazilas. In case of fomlation ofY AMC achievement was from 84 to 100% in the project areas. Success in fulfilling the target of organizing meeting in the committees ranged from 63 to 95% in the villages of the project areas. The following issues were encountered during the course of the project implementation below. • Number of communication materials like routine card, flash card, leaflet, posters were not adequate in number. • Although training was arranged for the communication officers of the project but there was no manual for using these materials in written fonn. • Although the Imams of the mosques were found very vital in disseminating the messages on arsenic it was not possible to give orientation and training due to inadequate logistics. • The owners of the restaurant or the teashop were found erasing red paint of the tubewells which were found arsenic and they marked those tubewells with green paints. • In few cases the members of the committees did not work spontaneously since there was no provision of incentive as they expected against their services.